The theory of subculture of the aging versus some social phenomena regarding senior citizens - Niezabitowski, Marek (Research on social problems in (pre-)pandemic reality, 2023)
For a long time, in the sociological discourse on the social situation of old people, there is a conviction that the distance between the generations is deepening. It appears in the reflections of both Polish and foreign gerontologists and sociologists. The theory of subculture of the aging is one of those reflections that took a condensed and structured form. The article will show the main assumptions of this theory according to Arnold Rose and some characteristic features of the social distinctiveness of older people in the light of Arlie Hochschild's research. They will be exhibited, among others, the factors favoring the formation of the old age subculture and areas of its functioning according to Rose, as well as some patterns of behavior observed by Hochschild among the members of the seniors’ subculture group studied by this researcher. The author will indicate certain processes that in Polish reality could / may favor the emergence of phenomena of a character of the old age subculture. The areas of social life related to the elderly and research topics or problems that may be inspired by the theory of subculture of the aging will be also introduced.